Noncontact reception of ultrasound from soft magnetic mild steel with zero applied bias field EMATs. (January 2022) - Rieger, Kai; Erni, Daniel; Rueter, Dirk
Abstract: Electromagnetic acoustic transducers (EMATs) without added magnets or bias currents receive ultrasound as bulk or Lamb waves from soft magnetic iron or mild steels. EMATs typically include bulky permanent or electromagnets for biasing magnetic fields in ultrasound reception. New compact-coils-only EMATs without additional magnets excite bias fields with pulsed strong coil currents, limiting detection time. Here, short premagnetization pulses in a simple EMAT coil allowed longer ultrasound reception from mild steel and virtually zero externally applied bias field. An unexpected long-lasting magnetic imprint inside the metal was clearly responsible and not normally expected with soft magnetic ferrous materials. Suggestions are made for mechanisms of electroacoustic coupling and permanent magnetization, even of transformer irons, after the termination of an exciting field. This contributes to novel applications of compact-coils-only EMATs without added magnets.